2018
DOI: 10.1371/journal.pone.0205791
|View full text |Cite
|
Sign up to set email alerts
|

High intensity resistance training causes muscle damage and increases biomarkers of acute kidney injury in healthy individuals

Abstract: PurposeHigh-intensity interval resistance training (HIIRT) is an increasingly popular exercise program that provides positive results with short sessions. This study aimed to evaluate whether an HIIRT session causes muscle and kidney damage.MethodsFifty-eight healthy volunteers (median age 24 years, 50% women) participated in this study and performed a HIIRT session. The Borg CR10 scale for pain (CR10P) and blood and urine samples were collected before (baseline) and 2 and 24 hours after the HIIRT session. Blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…Elevation of uIL-6 and uIL-8 was also found by Sugama et al after a duathlon [59]. Spada et al found an increase in uIL-18 after a HIIT session [48]. Dutheil et al found an increase in uIL-8 after a 24 h work shift and, according to the author, this elevation was related to stress [60].…”
Section: Urinary Interleukinsmentioning
confidence: 53%
See 3 more Smart Citations
“…Elevation of uIL-6 and uIL-8 was also found by Sugama et al after a duathlon [59]. Spada et al found an increase in uIL-18 after a HIIT session [48]. Dutheil et al found an increase in uIL-8 after a 24 h work shift and, according to the author, this elevation was related to stress [60].…”
Section: Urinary Interleukinsmentioning
confidence: 53%
“…In 5/29 females, uNGAL/uCr exceeded 100 ng/mgCr, the value of which is compatible with clinical AKI. In men, the increase in uNGAL and uNGAL/uCr was not statistically significant [48].…”
Section: Changes In Ungal After Exercises Shorter Than a Marathonmentioning
confidence: 70%
See 2 more Smart Citations
“…These results are consistent with those of strength training, which were shown to increase CK levels in 58 individuals after performing 4 min of high-intensity interval resistance training. The high-intensity interval resistance training session consisted of eight sets of squats performed with the fastest speed and highest number of repetitions achievable for 20 s, with 10 s of rest between sets (Spada et al, 2018 ). Moreover, it seems that CK decreases after 72 h (Tibana et al, 2019a ), for which we speculate that after 3 successive days of competition, athletes adapt to high-intensity stimuli.…”
Section: Discussionmentioning
confidence: 99%